The Influence of Digital Marketing and Electronic Word of Mouth (e-WOM) on Purchase Intention on the Tokopedia Application - Fauzan, Adam Jordan (Proceeding of International Management Conference and Progressive Papers, 2024)
In the current era of globalization, communication technology and the internet are developing very quickly. Thus, it has caused changes in various community activities, including purchasing behavior. People are starting to switch from conventional shopping (offline) to shopping online as a result of the increasing use of e-commerce such as Tokopedia, which is one of the first e-commerce providers in Indonesia. So this study aims to analyze the influence of digital marketing and electronic word of mouth (e-WOM) on purchase intention on the Tokopedia application. The theory in this study is to use social media marketing and marketing mix. This study uses a quantitative approach. The data collection technique used is distributing questionnaires and documentation. The respondents used in this study are people who will do research on the Tokopedia application. The research sample used a purposive sampling technique with a total of 110 respondents with criteria with an age range of 18-43 years. The data analysis technique used in this study is multiple linear regression analysis using SPSS 25. The results of this study show that digital marketing and electronic word of mouth (e-WOM) have a positive and simultaneous effect on purchase intention on the Tokopedia application.